Analisis Likuefaksi Berdasarkan Data CPT Untuk Perancangan Pondasi Di Pesisir Pantai Kabupaten Kulon Progo DIY - Anggara, Vebrian; Fatnanta, Ferry; Yusa, Muhamad (Civil Engineering Departement, Andalas University, 2020)
Yogyakarta Special Region (DIY) is an area that has a high level of seismic activity in Indonesia. This is due to various local faults near the land and its location adjacent to the subduction of the Indo-Australian and Eurasian plates. The proposed new airport is located on the coast in Kulon Progo Regency DIY. The location is dominated by the sands layer and it has high ground water levels which indicate the high potential of liquefaction. The site classes of the coast in Kulon Progo Regency is medium category (SD). Liquefaction analysis using the PGAM value of 0.4 g. Liquefaction has the potential to occur in soil layers 0 - 6 meters. The analysis shows for eartquake of ≥ 6.3 Mw has a very high category of liquefaction. The analysis results has LPI ≥ 29.30 for ground water conditions at the surface, and LPI ≥ 15.32 for ground water conditions in depths of 3 meters. Estimated soil settlements of 19.7 cm for magnitude of 8.1 Mw with ground water conditions at the surface. The use of shallow foundations at soil depths of 0-6 meters is not recommended, unless a soil improvement method is used to eliminate the potential for liquefaction.